MSMES RISES TO THE NEXT LEVEL WITH HALAL CERTIFICATION BY MUHAMMADIYAH BUSINESS ACTORS IN CANDI SIDOARJO BRANCH - Handayani, Puspita; Ramadhani Nurbaya , Syarifah; Nur Khofifah , Nisa’; Abror, M; Raissa Gardiana , Gladys (Antis-publisher, 2025)
Objective: This study aims to emphasize the crucial role of halal certification programs in advancing micro, small, and medium enterprises (MSMEs) to the next level. MSME development is an indicator of increased productivity, ensuring sustainable marketing. Halal certification serves as an effective communication tool for consumers to identify halal products, aligning with the mandates of Indonesian Law Number 33 of 2014 on Halal Product Assurance. Method: The community service initiative was conducted in the Candi District, Sidoarjo Regency, targeting MSMEs in collaboration with Muhammadiyah Candi branch members. The program included two main stages: socialization and assistance. Socialization sessions were held at Kedung Peluk Village’s BUMDes and covered the Islamic perspective on halal, relevant regulations, the halal certification application process via the information system http://ptsp.halal.go.id, Halal Product Assurance System (SJPH) documentation, and practices to maintain product halal status. Results: As a result of the initiative, MSME participants gained comprehensive knowledge about the halal certification application process, familiarity with the information system used for application, and the ability to prepare and manage SJPH documentation to ensure their products' halal status. Novelty: This program uniquely combines practical assistance and educational outreach tailored for MSMEs in a specific local context. By addressing gaps in awareness and procedural knowledge about halal certification, the initiative not only bridges informational divides but also empowers MSMEs to align with national halal product assurance regulations effectively.